Diallyl trisulfide (DATS) abrogates arsenic induced testicular oxidative stress in rats - Prabu, Selvaraj Milton; Sumedha, Naorem (International Journal of Pharmacology and Toxicology, 2014)
Background: Arsenic is an emblematic heavy metal and enters the animals through intake of arsenic contaminated water and gets stored in primitive organs. Aim: The present study was designed to investigate the protective effect of diallyl trisulfide (DATS) on arsenic (As) induced testicular oxidative stress in male rats. Methods: Experimental rats were randomly divided into four groups and treated orally for 28 days: control, as (5mg/kg/bw) treated, DATS (80mg/kg/bw) + As treated and DATS (80mg/kg/bw) alone treated rats. Testicular toxicities were recorded by plasma hormonal analysis, sperm function test, estimation of testicular oxidative stress markers, biochemical analysis, antioxidant enzymes and non-antioxidant enzymes and histopathological changes. Results: Short term exposure to as resulted in decreased testicular - weight; sperm count, plasma hormonal concentration and significantly increased levels of oxidative stress markers, testis ALP, ACP and cholesterol with a significant decreased in the enzymatic antioxidant, non-antioxidant enzymes and ATPases enzymes when compared to the control group. Pre-administration of DATS to as treated rats were found to protect against adverse changes in the reproductive organ weight, sperm count, enhance plasma hormone level along with restored antioxidant enzymes, non-antioxidant enzymes and ATPases enzymes supporting with revived histological structure of testes. Conclusion: Our results show that DATS exerts a protective effect against as induced testicular toxicity associated with reduced testicular oxidative stress as evidenced by the clear restoration of plasma hormone levels and antioxidant activities. Keywords: Arsenic, Diallyl Trisulfide, Oxidative Stress, Rat, Testis.